2014
DOI: 10.1111/irv.12243
|View full text |Cite
|
Sign up to set email alerts
|

HIV virological suppression influences response to the AS03‐adjuvanted monovalent pandemic influenza A H1N1 vaccine in HIV‐infected children

Abstract: DesignChildren with HIV are especially susceptible to complications from influenza infection, and effective vaccines are central to reducing disease burden in this population. We undertook a prospective, observational study to investigate the safety and immunogenicity of the inactivated split-virion AS03-adjuvanted pandemic H1N1(2009) vaccine in children with HIV.SettingNational referral centre for Paediatric HIV in Ireland.SampleTwenty four children with HIV were recruited consecutively and received two doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…A previous study showed that poor seroprotection of the influenza vaccine was associated with high dVL (RNA > 40 copies/mL) in HIV-infected children [ 30 ]. In addition, Leahy et al showed that a high proportion of RNA ≤ 40 copies/mL was associated with a low incidence of ILI, because children on HAART with full virologic suppression were more likely to sustain a robust serological response to the vaccine [ 31 ]. These findings suggest that influenza vaccination given during a virologic suppression increases the immunogenicity of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that poor seroprotection of the influenza vaccine was associated with high dVL (RNA > 40 copies/mL) in HIV-infected children [ 30 ]. In addition, Leahy et al showed that a high proportion of RNA ≤ 40 copies/mL was associated with a low incidence of ILI, because children on HAART with full virologic suppression were more likely to sustain a robust serological response to the vaccine [ 31 ]. These findings suggest that influenza vaccination given during a virologic suppression increases the immunogenicity of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…HIV greatly increased the risk of influenza virus-associated SARI in children, and therefore yearly influenza vaccination should be considered in routine pediatric HIV clinical care. Influenza vaccination in HIV-infected children is safe, but it has low efficacy (<20%) and may only be immunogenic in older children and adolescents with virological suppression [36][37][38]. Viral coinfection was common, with 1 coviral cluster associated with clinical severity in SARI cases.…”
Section: Discussionmentioning
confidence: 99%
“…Many national health authorities recommend immunisation of HIV+ individuals against influenza due to potential for increased susceptibility and/or disease severity 19 . Conventional or adjuvanted influenza vaccines are immunogenic in HIV+ adults 20 21 22 23 and children 24 25 26 27 , however the induction and maintenance of influenza-specific antibody titres is frequently lower than in comparable HIV− controls, particularly in the absence of ART or in infected subjects with low CD4 T cell counts 24 26 28 29 30 31 . Similarly, the establishment of influenza vaccine-elicited memory B cell responses, as measured by polyclonal stimulation and B cell ELISpot, are diminished compared to healthy controls 12 .…”
mentioning
confidence: 99%